DESIGN AND RISK ASSESSMENT ANALYSIS OF SUBSEA PIPELINE IN NATUNA SEA - Azzahra, Nada
Oil and natural gas are still the main sources of energy that support our life. In Indonesia, oil and gas exploration and exploitation activities continue to grow rapidly and are generally carried out offshore. Subsea pipelines are an effective and efficient solution for massive and sustainable fluid distribution. In general, the fluids that flow through subsea pipelines are toxic or can pollute the environment and are dangerous for humans. Therefore, it is necessary to design and analyze the pipeline based on the applicable quality standards. The design stages are carried out to determine the wall thickness of the subsea pipe based on the DNVGL-ST-F101 standard, to determine the lateral stability and vertical stability based on the DNV-RP-F109 standard, to determine the lay-barge configuration in the installation process based on the applicable stress limits, and to determine the span length permitted under the DNV-RP-F105 standard. After that, an analysis of the risk of subsea pipeline failure due to external events that may occur is carried out based on the DNV-RP-F107 standard. Based on the design process carried out, the subsea pipeline wall thickness is 14.3 mm, the concrete layer thickness to achieve stability on the seabed is 45 mm, and the allowed free span length is 13.60 m. The lay-barge configuration in the installation process is carried out with the PLB Hafar Neptune ship with a hitch angle of 0o and a trim barge angle of 0.6o. Installation modeling obtained the maximum stress in the overbend area of 84.62% and in the sagbend area of 25.4%. Subsea pipeline risk analysis is seen for dropped anchor and sinking vessel failure scenarios based on the DNV-RP-F107 standard using ship arrival data for 1 year from the Port of Singapore, Batu Ampar Port, and Tanjung Pelepas Port. The results of the analysis show that the level of risk of subsea pipeline failure in Natuna waters is in the acceptable, ALARP, and not acceptable area.